PENINGKATAN KAPASITAS PRODUKSI DAN STRATEGI PEMASARAN USAHA KECIL DAN MENENGAH (UKM) SIRUP BUAH PALA DI NEGERI BOOI, PULAU SAPARUA - Hermi Oppier; Hendri Dony Hahury; Selvenco Tuasuun (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Small and Medium Entreprises (SMEs) play important and strategic roles in the regional economy, as well as at the national level. The SMEs refer to productive public economic operations proven to be resilient in times of crises. At the regional level, the presence of SMEs has indirectly absorbed labor and lowered unemployment, which is a constraint to economic progress. However, at the regional level, they face insignificant challenges in expanding their business, particularly in terms of production capacity and marketing strategy. The Community Service Team of Department of Development Economics of Faculty of Business and Economics of Pattimura University, provided training and science and technology diffusion. The training was delivered through counseling on improving the production capacity and marketing strategy while the science and technology diffusion was spread through the development of nutmeg syrup products. Outcomes of the Community Service activity included identifying the potential and problems developing the SMEs, as well as providing solutions by providing a more appealing container for the nutmeg syrup than the previous one, and increasing group members’ knowledge of increasing the production capacity and marketing strategy for the nutmeg syrup products.